Distinct conformations of the HIV-1 V3 loop crown are targetable for broad neutralization - Nikolas Friedrich (Nature Portfolio, 2021)
The V3-crown of the HIV-1 envelope protein largely elicits non-neutralizing antibodies. Here, the authors show that the V3-crown can be targeted by broadly neutralizing designed ankyrin repeat proteins recognizing two conformations one of which resembles CCR5- bound V3.